The versatility of lignocellulosic composition in oil palm trunks influences the adsorption capacity of derived biochar - Hakimi, Mohd Idham; Mohd Yusoff, Mohd Zulkhairi; Zakaria, Mohd Rafein; Norrrahim, Mohd Nor Faiz; Yoshihito, Shirai; Hassan, Mohd Ali (Springer Science and Business Media Deutschland GmbH, 2024)
Oil palm trunks (OPT) are a valuable but often mismanaged resource in plantations, typically left to decompose, causing pest issues and harming soil health. Transforming OPT into biochar, a promising bioadsorbent, addresses environmental challenges while creating a secondary income stream. This study examines the versatility of OPT’s lignocellulosic composition for biochar production. OPT was divided into bark (OPTB), peripheral (OPTP), and core (OPTC). The properties of these parts were compared before and after carbonization, followed by methylene blue (MB) adsorption analysis. Results showed that OPTB had the highest lignin content at 13.6 wt%, compared to 9 wt% in OPTP and 1.3 wt% in OPTC, with insignificant differences in holocellulose content among the parts. OPTC was notable for its high starch content, reaching 9.2 wt%. Surface analysis of OPT biochar revealed that OPTP-Bc had the highest surface area at 3.27 m²/g, followed by OPTC-Bc at 3.07 m²/g, and OPTB-Bc at 2.69 m²/g. The adsorption analysis showed that OPTC-Bc achieved a 92.8% removal efficiency using a dosage of 4 g/L, indicating its effectiveness in adsorbing MB. The results aligned with established models, including Langmuir (R² = 0.93), Freundlich (R² = 0.98), and Temkin (R² = 0.99). These results demonstrate that the lignocellulosic composition of oil palm trunks significantly influences the surface characteristics of the produced biochar, enhancing its potential as a bioadsorbent. This study highlights the promise of sustainable agricultural practices to convert biomass waste into valuable assets, fostering a greener and more economically vibrant future.